Integrating high-speed treadmills into a traditional strength and conditioning program for speed and power sports - Hauschildt, M. (Strength and Conditioning Journal, 2010)
HIGH-SPEED TREADMILLS HAVE BECOME VALUABLE TOOLS FOR INCREASING SPEED AND SPORTS PERFORMANCE OVER THE PAST 2 DECADES. TRADITIONALLY, THEY HAVE BEEN PART OF NARROWLY FOCUSED CLINIC-BASED PROGRAMS DESIGNED TO INCREASE SPEED SOLELY WITH THE USE OF TECHNOLOGY. THIS HAS LED TO QUESTIONS ABOUT SURFACE TRANSFER, HIGH INJURY RATES, AND HOW THIS TECHNOLOGY FITS INTO A COMPREHENSIVE STRENGTH AND CONDITIONING PROGRAM. HERE, WE WILL NOT ONLY ADDRESS THESE ISSUES BUT ALSO DEMONSTRATE THAT WHEN PROPERLY INTEGRATED, HIGH-SPEED TREADMILLS ARE EXCEPTIONAL TOOLS THAT CAN BE USED IN A VARIETY OF SETTINGS TO IMPROVE PERFORMANCE FOR THE SPEED AND POWER ATHLETES WHILE ALL BUT ELIMINATING SPRINT-RELATED INJURIES.